Peran Perilaku Hidup Bersih dan Sehat (PHBS) dalam Pencegahan Penularan Tuberkulosis Melalui Implementasi Cekoran Bu Titik (Cegah Resiko Penularan Melalui Batuk Efektif Dan Etika Batuk) - Erna Safitri; Wada Islami; Sela Safitri; Ade Rahma Azizah; Mulia Utari; Intan Safitri; Maulidar Maulidar (JURNAL RISET RUMPUN ILMU KESEHATAN, 2025)
Tuberculosis (TB) is currently a public health problem in the world, especially in Indonesia. Pulmonary TB is ranked 2nd as the main cause of death from infectious diseases after Human Immuno deficiency Virus (HIV). Pulmonary Tuberculosis is easily spread through the air when people who are sick with Pulmonary Tuberculosis release bacteria through the coughing mechanism. The spread of these bacteria is through sputum splashes or droplet nuclei released by TB sufferers through coughing, sneezing or talking face to face. The increase in TB cases is related to the degree of health in the community. The biggest factors that affect the degree of health are environmental factors and community behavior itself which can be detrimental to health. Risk factors for Tuberculosis transmission are environmental factors and behavioral factors, environmental factors include ventilation, housing density, temperature, lighting and humidity. While behavioral factors include smoking habits, spitting or throwing phlegm anywhere, coughing or sneezing without covering the mouth and the habit of not opening windows and not implementing clean and healthy living behavior (PHBS). This research method is a quantitative study with statistical tests with a cross-sectional design. This study was conducted at SMP 4 Ulee Rubek, North Aceh in November 2024. The research sample consisted of 15 children, Data collection techniques using questionnaires. Data analysis used descriptive statistical tests to test adolescents' knowledge about how to prevent TB. In addition to effective coughing, there are several ways to control pulmonary tuberculosis, namely by cultivating a clean and healthy life and cultivating ethical coughing behavior.